2015
DOI: 10.1149/2.0741504jes
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Calorimetry: Analytical Tool for In-Situ Characterization of Lithium Ion Batteries

Abstract: Thin-Film Calorimetry (TFC) as presented in this work is a novel analytical tool to determine phase transformation temperatures and enthalpies of thin films and thin-film sequences. The key component is a high-temperature stable piezoelectric langasite (La 3 Ga 5 SiO 14 ) resonator serving as a highly sensitive planar temperature sensor. Deviations in its frequency are related to temperature fluctuations caused by phase transformations and used to calculate the related enthalpies. Temperature ramps from room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The reasons for these differences are still not fully understood. In publications focused on these phase transformations, it is reported that the stoichiometric spinel phase crystallizes from different parent phases in different atmospheres, even though the starting composition is the same. The TFC results show that the phase mixture in the low‐ p O2 atmosphere has a higher thermal stability than the over‐stoichiometric spinel, which is the parent phase in the atmosphere with higher oxygen partial pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for these differences are still not fully understood. In publications focused on these phase transformations, it is reported that the stoichiometric spinel phase crystallizes from different parent phases in different atmospheres, even though the starting composition is the same. The TFC results show that the phase mixture in the low‐ p O2 atmosphere has a higher thermal stability than the over‐stoichiometric spinel, which is the parent phase in the atmosphere with higher oxygen partial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The TFC results show that the phase mixture in the low‐ p O2 atmosphere has a higher thermal stability than the over‐stoichiometric spinel, which is the parent phase in the atmosphere with higher oxygen partial pressure. A detailed introduction to the technique and detailed results of the LMO characterization are published elsewhere . These results are in good agreement with the annealing behavior of the PLD‐deposited LMO films presented here, where a single‐phase sample is prepared at an annealing temperature of 700 °C, which is in between the two values from TFC characterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thin-Film Calorimeter (TFC) is a measurement system for the determination of temperature and enthalpy of phase transformations (PT) of thin films. Its suitability to provide thermodynamic data in the field of LIB materials has been demonstrated [9], [10], [11], [12]. It uses piezoelectric langasite (La3Ga5SiO14, LGS) resonators which serve as planar temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar stress effects have been noted at phase transformations that are accompanied by large volume changes. 21 To exclude or reduce the effect of mechanical deflection stress, PCO films of nearly identical thicknesses were deposited on both sides of the resonators.…”
mentioning
confidence: 99%